Przemieszczenie soczewki u dzieci - Kanigowska, Krystyna; Grałek, Mirosława (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Ectopia lentis in children continues to be a diagnostic and therapeutic challenge for ophthalmologists. It can occur in isolation, in association with other ocular disorders or as part of systemic disorder. Marfan’s syndrom and homocystinuria are the most frequent cause of heritable ectopia lentis. The authors describe ocular findings and clinical symptoms diseases with ectopia lentis. Differential diagnostic and treatment methods are discussed.